Analisis Hubungan Pola Makan dengan Kejadian Anemia pada Mahasiswa Keperawatan Semester IV - Maulia Ananda Karisma; Nutrisia Nu’im Haiya; Iwan Ardian (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Background: Anemia is often a health problem experienced by many students, mainly due to an unbalanced diet and a lack of essential nutrients, such as iron, which the body needs. Nursing students, as future health workers, should be highly aware of the importance of a nutritious diet to support their health and academic performance. This study is useful for determining the relationship between diet and the incidence of anemia in fourth-semester nursing students at Sultan Agung Islamic University in Semarang. Methods: This study adopted a correlational descriptive design with a cross-sectional approach. The population consisted of 173 fourth-semester students from the Faculty of Nursing, with a sample of 121 respondents selected purposively. Data were collected using a dietary questionnaire and hemoglobin level tests, then analyzed using the Chi-Square test. Results: The majority of students had poor dietary patterns (41.3%), but 81 respondents (66.9%) still experienced anemia. The output of the Chi-Square test revealed a significant relationship between dietary patterns and the incidence of anemia (p-value = 0.001). In conclusion, there is an important relationship between dietary patterns and the incidence of anemia among fourth-semester nursing students. Students who have poor dietary patterns tend to have a higher risk of anemia. Efforts are needed to raise nutritional awareness through education and the promotion of balanced dietary habits on campus.